Respuesta :

Answer:

a = -1

Step-by-step explanation:

Solve for a:

a + 2 = 4 a + 5

Subtract 4 a from both sides:

(a - 4 a) + 2 = (4 a - 4 a) + 5

a - 4 a = -3 a:

-3 a + 2 = (4 a - 4 a) + 5

4 a - 4 a = 0:

2 - 3 a = 5

Subtract 2 from both sides:

(2 - 2) - 3 a = 5 - 2

2 - 2 = 0:

-3 a = 5 - 2

5 - 2 = 3:

-3 a = 3

Divide both sides of -3 a = 3 by -3:

(-3 a)/(-3) = 3/(-3)

(-3)/(-3) = 1:

a = 3/(-3)

The gcd of 3 and -3 is 3, so 3/(-3) = (3×1)/(3 (-1)) = 3/3×1/(-1) = 1/(-1):

a = 1/(-1)

1/(-1) = -1:

Answer:  a = -1